Estudo de casos sobre a inércia térmica de edificações na cidade de São Carlos - Dornelles, Kelen Almeida (Universidade Federal de São Carlos, 2004)
In this work, it was investigated the use of thermal inertia in buildings located in Sao Carlos city, SP, which presents semi-humid climate. This research aims to verify the hypothesis that the use of thermal inertia in buildings submitted to the specific climate of Sao Carlos allows to optimize the thermal performance of buildings and to reduce waste of energy to restore indoor thermal comfort. From data obtained by monitoring of seven different buildings, the thermal performance of each one was analyzed when they are submitted to typical simmer and winter conditions. To these seasons, adopting a reference day , it was estimated the heating and cooling requirement to restore the indoor comfort conditions. Besides the analyses for winter and summer seasons, it was estimated the indoor cooling and heating requirement along all moths of the year. Through this analyze, it was possible to verify the real influences of thermal inertia on the indoor comfort conditions. The results indicates that only the use of thermal inertia is insufficient to provide indoor thermal comfort conditions for buildings submitted to the specific climates of Sao Carlos. It is suggested to mach the use of thermal inertia with others passive strategies, in such a way to optimize the thermal performance of buildings.
Case study of buildings thermal inertia in Sao Carlos, SP
Keywords: Arquitetura e conservação de energia; Inércia térmica; Conforto térmico; Materiais de construção; Thermal inertia; Thermal comfort; Thermal and energetic performance of buildings; Building systems; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL